(E)-4,2′,4′-Trimethoxychalcone (Z)-N-Tosyl Hydrazone - Sonia Berenguel Gómez; Irene Moreno-Gutiérrez; Manuel Muñoz-Dorado; Míriam Álvarez-Corral; Ignacio Rodríguez-García (Molbank)
The synthesis and structural characterization of (E)-4,2′,4′-trimethoxychalcone (Z)-N-tosyl hydrazone, a conjugated tosylhydrazone derivative, is described. The compound was obtained via the condensation of (E)-1-(2,4-dimethoxyphenyl)-3-(4-methoxyphenyl)prop-2-en-1-one with p-toluenesulfonylhydrazide in methanol under mild conditions, yielding a yellow solid in a 66% yield. The structure of the product was confirmed through 1H NMR, 13C NMR, IR spectroscopy, mass spectrometry, and single-crystal X-ray diffraction analysis, which revealed a non-planar molecular conformation and a Z configuration for the C=N double bond. This work is part of our ongoing research on carbene-mediated transformations.